The Review of Action Learning Approach Formulae Heutagogical Practice in Civil Engineering and Construction Studies - Mokhothu, Khojane Geoffrey (Research in Social Sciences and Technology, 2026)
The Action Learning Approach (ALA) is a teaching method that promotes learning by doing. ALA encourages full students’ engagement through interaction with peers in groups and with lecturers. In Civil Engineering and Construction Studies, teamwork is emphasised in both theoretical (content knowledge) and practical learning processes. Heutagogy, on the other hand, is a learning strategy that fosters self-driven learning through active practical involvement. It aims to cultivate students’ critical thinking, innovation, creativity, as well as their problem-posing and problem-solving skills. Within technical and vocational education, as well as engineering and technology education, the steps of the technological process play a central role in teaching and learning. The purpose of this study was to review existing action learning approach formulae and models to enhance the integration of theoretical (content knowledge) and practical work in Civil Engineering and Construction Studies. The main objective was to develop an action learning formula to support lecturers in applying action learning methods for quality teaching that integrates theory and practice. A systematic evaluation of available empirical evidence, along with a critical and comprehensive review of existing data, was carried out to inform the study. The review analysed the action learning approach through the lens of six steps of the technological process. Furthermore, the study recommends that heutagogy be adopted as the primary strategy for implementing action learning, in order to strengthen the integration of content knowledge and practical work in Civil Engineering and Construction Studies, and more broadly within the built environment disciplines.